2009
DOI: 10.1016/j.str.2008.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Gating Mechanism of the Influenza A M2 Channel Revealed by 1D and 2D IR Spectroscopies

Abstract: Summary The pH-controlled M2 protein from Influenza is a critical component of the virus, serving as a target for aminoadamantane anti-flu agents that block its H+ channel activity. To better understand its H+-gating mechanism, we investigated M2 in lipid bilayers with a new combination of IR spectroscopies and theory. Linear FTIR spectroscopy was utilized to measure the precise orientation of the backbone carbonyl groups, and 2D-IR spectroscopy was utilized to identify channel-lining residues. At low pH (open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
172
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(188 citation statements)
references
References 42 publications
7
172
2
5
Order By: Relevance
“…For example, a change of ∼50% was observed between a solvated and a hydrophobic site in the M2 tetramer. 32 Despite the relatively small variation, this result suggests that the lifetime of the amide I vibration is sensitive to changes in the local solvent density. 32 As shown (Figures 4(a) and 4(b)), the amide I vibrational lifetimes of Ala30 and Gly34, which were determined by examining the decay of the respective 2D IR peak intensity with waiting time, are identical.…”
Section: B 2d Ir Spectramentioning
confidence: 94%
See 2 more Smart Citations
“…For example, a change of ∼50% was observed between a solvated and a hydrophobic site in the M2 tetramer. 32 Despite the relatively small variation, this result suggests that the lifetime of the amide I vibration is sensitive to changes in the local solvent density. 32 As shown (Figures 4(a) and 4(b)), the amide I vibrational lifetimes of Ala30 and Gly34, which were determined by examining the decay of the respective 2D IR peak intensity with waiting time, are identical.…”
Section: B 2d Ir Spectramentioning
confidence: 94%
“…32,[49][50][51] However, it should be noted that the variation in the amide I vibrational lifetimes of proteins is generally small. For example, a change of ∼50% was observed between a solvated and a hydrophobic site in the M2 tetramer.…”
Section: B 2d Ir Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The 2DIR technique distinguishes β-sheet structures by producing Z shape like spectra [18,19] when this particular structural motif is present. In the past decades a number of 2DIR studies have been reported of peptides and proteins in solution [16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] or confined in membranes [34][35][36][37][38], revealing structural details and conformational changes from femtosecond (fs) to nanosecond (ns) time scales, and the nature of dynamic environments. For the structure determination of peptides that are in gas phase or micro-solvated (surrounded by few solvent molecules) the mid-infrared spectroscopic technique has become a promising tool [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The only difference is the vastly disparate timescales probed by the two methods -picoseconds versus milliseconds -, which refers to the "direct time resolution" inherent to both techniques. In the context of protein dynamics, 2D IR spectroscopy has been applied to investigate the structure of membrane peptides [21,22], fibril formation [23,24], the structural flexibility of enzyme active sites [25], ligand migration in heme proteins [26], ligand binding [27,28], and the dynamics of the protein hydration shell [29,30], to list just a few examples. Recent reviews can be found in Refs.…”
Section: Advancing the Sensitivitymentioning
confidence: 99%